2020
DOI: 10.1136/bmjsem-2020-000850
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and correlates of physical activity in a sample of UK adults observing social distancing during the COVID-19 pandemic

Abstract: ObjectiveTo investigate the levels and correlates of physical activity during COVID-19 social distancing in a sample of the UK public.MethodsThis paper presents analyses of data from a cross-sectional study. Levels of physical activity during COVID-19 social distancing were self-reported. Participants also reported on sociodemographic and clinical data. The association between several factors and physical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
115
3
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 92 publications
(139 citation statements)
references
References 12 publications
(9 reference statements)
20
115
3
1
Order By: Relevance
“…As many other opportunities for physical activity were also curtailed during lockdown (e.g., sport and gyms for people and sporting activities for dogs) the impact on physical wellbeing for both species were likely to have been substantially affected. The potential for a decrease in physical activity (PA) amongst people during the COVID-19 pandemic has been recognised [ 30 ] and advice published regarding how best to achieve recommended levels of PA during these unprecedented times [ 31 , 32 , 33 ]. Similarly, for dogs, the physical health benefits of walking are well recognised, for example to reduce the risk of obesity [ 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…As many other opportunities for physical activity were also curtailed during lockdown (e.g., sport and gyms for people and sporting activities for dogs) the impact on physical wellbeing for both species were likely to have been substantially affected. The potential for a decrease in physical activity (PA) amongst people during the COVID-19 pandemic has been recognised [ 30 ] and advice published regarding how best to achieve recommended levels of PA during these unprecedented times [ 31 , 32 , 33 ]. Similarly, for dogs, the physical health benefits of walking are well recognised, for example to reduce the risk of obesity [ 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Time spent in MVPA was assessed by two questions, as used in a previous study ( Smith et al., 2020 ) : 1) “How much time on an average day have you spent in vigorous physical activity since self-isolating?”; and 2) “How much time on an average day have you spent in moderate physical activity since self-isolating?”. For the logistic models, MVPA and MPA were dichotomized into 1=<30 min per day, or 2=≥30 min/day, and VPA was dichotomized into 1=<15 min/day, or 2=≥15 min of VPA/day.…”
Section: Methodsmentioning
confidence: 99%
“…On the other hand, sedentary behavior (SB) is associated with depressive ( Hallgren et al., 2020 ; Zhai et al., 2015 ) and anxiety symptoms ( Teychenne et al., 2015 ). However, it is seen that during self-isolation, physical activity levels decreases ( Ammar et al., 2020 ; Lesser and Nienhuis, 2020 ; Meyer et al., 2020 ; Rogers et al., 2020 ; Smith et al., 2020 ; Stanton et al., 2020 ) while time spent in SB increases ( Meyer et al., 2020 ; Qin et al., 2020 ; Rogers et al., 2020 ; Stanton et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…A recent study among adults in the UK showed limited physical activity experienced during the application of COVID-19 related social distancing measures. 14 Another study from Brazil showed reduced moderate to vigorous physical activity and increased SB during the application of COVID-19 related social distancing measures. 15 Such changes in lifestyle during the COVID-19 crisis might have long-term effects on health, subsequently the body response to infections.…”
Section: Introductionmentioning
confidence: 99%